Education as the Foundation of Human Development: Ibn Sina’s Educational Thought and Its Relevance to Contemporary Islamic Education - Alif Bagus Fitriadi; Moh. Buny Andaru Bahy; Lulur Rochmawati; Hendra Setiawan (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
This article discusses Ibn Sina’s educational thought and its implications for contemporary Islamic education. Ibn Sina, who has long been recognised as a philosopher and an expert in medicine, is also found to have developed significant ideas concerning the concept of Islamic education. His educational thought provides constructive and solution-oriented contributions to current educational challenges. The research method employed in this study is descriptive qualitative, aiming to explain and understand Ibn Sina’s educational thought in depth. The findings reveal several important aspects. First, according to Ibn Sina, the objectives of education are directed toward the development of the physical, intellectual, and moral dimensions of the learner. Second, the curriculum, as conceptualised by Ibn Sina, may be classified according to age groups: ages 3–5 years, 6–14 years, and 14 years and above. Third, the teaching methods proposed by Ibn Sina include talqin (guided instruction), demonstration, habituation and exemplary modelling, discussion, apprenticeship, assignments, as well as targhib (encouragement) and tarhib (discouragement). Finally, Ibn Sina emphasised the character of an ideal educator, who should be religious, intelligent, competent in teaching children, capable of cultivating moral education, cheerful in demeanour, calm in appearance, polite, courteous, clean, pure, and free from bullying or frivolous behaviour in front of students.